CIDADANIA PARA TODOS - ALBRECHT, DIEGO A. S.; HAUSER, ESTER E.; PADOIN, FABIANA F.; GATTO, JOAQUIM H.; NIELSSON, JOICE G.; BAGATINI, JÚLIA; RAMOS, LIZÉLIA T.; SILVA, NILVA H. D. (Salão do Conhecimento, 2013)
Resumo